Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.inorgchem.1c01897
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity and Incompatibility Induced Complex Phase Formation Behavior in the Stuffed Tridymites Ca1–xSrxGa2O4

Abstract: Stuffed tridymites AM 2 O 4 composed of a condensed MO 4 -tetrahedra-based framework have been widely investigated due to their structural diversity and rich physical properties. Herein, the strategy of stuffing mixed Ca 2+ and Sr 2+ cations into the [Ga 2 O 4 ] 2− framework in (Ca 1−x Sr x )Ga 2 O 4 (CSGO, 0 ≤ x ≤ 1) is utilized to manipulate the phase formation behavior with different structure types at particular annealing temperatures. Five derivatives, including αand β-CaGa 2 O 4 , βand γ-SrGa 2 O 4 , and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Such a 3D network structure without non-bridging oxygens leads to robustness toward air and moisture. Furthermore, there are cage-like void spaces with diameters of 5–6 Å surrounded by Ba 2+ ions in the lattice (Figure b) . Such crystallographic voids are suitable for the stabilization of anionic electrons .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a 3D network structure without non-bridging oxygens leads to robustness toward air and moisture. Furthermore, there are cage-like void spaces with diameters of 5–6 Å surrounded by Ba 2+ ions in the lattice (Figure b) . Such crystallographic voids are suitable for the stabilization of anionic electrons .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are cage-like void spaces with diameters of 5−6 Å surrounded by Ba 2+ ions in the lattice (Figure 1b). 18 Such crystallographic voids are suitable for the stabilization of anionic electrons. 9 If the lattice O 2− sites can be replaced by H − ions, then electrons are expected to be accommodated in the interstitial cage sites (Figure 1b), as shown in eq 1, to preserve the charge balance because neither Ba 2+ nor Al 3+ has other oxidation states.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Herein, we shift our attention to a family of Bi 3+ -activated tridymite-type gallates AGa 2 O 4 (A = Ba 2+ , Sr 2+ , Ca 2+ ), where the structural symmetry strongly depends on the A-cation size, as presented in Table 1. [25][26][27][28][29] The structural diversity of these gallates generates various coordinating environments for the A-sites, which is suitable for the accommodation of Bi 3+ ions, thereby leading to tunable emission wavelengths for AGa 2 O 4 : Bi 3+ phosphors. For instance, Lin et al reported that Ba 1+x Sr 1−x Ga 4 O 8 :Bi 3+ phosphors exhibit extremely broadband spectra, covering the spectral range from purple-blue to deep red (350-900 nm).…”
Section: Introductionmentioning
confidence: 99%